Pengembangan Instrumen Tes Kemampuan Berpikir Tingkat Tinggi Tema Energi Ramah Lingkungan Pada Siswa Kelas IX - Ashri Fathia; Liska Berlian; R. Ahmad Zaky El Islami (UNIB Press, 2023)
The problem with test instruments made by teachers tends to test more aspects of memory without honing the ability to think at a high level of students is what prompted this research. The purpose of this study was to develop a high level thinking test instrument designed for grade IX students on the theme of environmentally friendly energy. The method used is Research and Development (R&D) consisting of potential problems, data collection, product design, design validation, design revision and product trials. This research resulted in the form of a high level thinking test instrument. The test instrument has been tested for feasibility based on expert validation obtaining a validity level of 98.36% (very valid) with details of material expert validation of 97.77% and science teacher experts of 98.96%. Based on the test of test instruments on 105 students measured by Anates software version 4.0.5, the results obtained 20 valid questions with moderate difficulty, reliability of 0.85 (high reliability) and good differentiating power as many as 5 questions and sufficient differentiating power as many as 15 questions. Therefore, it can be concluded that the test instrument with an overall product efficiency value obtained based on student responses is 89.12% (very efficient). Â The results of the development of test instruments can be used for further research that will measure the level of ability with high level thinking in class IX students on the theme of environmentally friendly energy.